Two Novel Phenylpropanoid Trimers From Ligusticum chuanxiong Hort With Inhibitory Activities on Alpha-Hemolysin Secreted by Staphylococcus aureus - Wan, Shi-Jie; Ren, Han-Gui; Jiang, Jia-Ming; Xu, Gang; Xu, Yu; Chen, Si-Min; Chen, Gan; Zheng, Dan; Yuan, Man; Zhang, Hong; Xu, Hong-Xi (Frontiers in Chemistry, 2022)
The emergence of antibiotic resistance in Staphylococcus aureus has necessitated the development of innovative anti-infective agents acting on novel targets. Alpha-hemolysin (Hla), a key virulence factor of S. aureus, is known to cause various cell damage and death. In this study, with bioassay-guided fractionation, a pair of unusual epimeric lignan trimers, ligustchuanes A and B (1 and 2), were isolated from the rhizomes of Ligusticum chuanxiong Hort, together with two known phthalides being identified by UPLC-QTOF-MS. To the best of our knowledge, trimers with rare C8-C9''-type neolignan and ferulic acid fragments have not been identified in any natural product. Both of them were isolated as racemic mixtures, and their absolute configurations were determined by comparing experimental and calculated ECD spectra after enantioseparation. Ligustchuane B exhibited an outstanding inhibitory effect on α-hemolysin expression in both MRSA USA300 LAC and MSSA Newman strains at concentrations of 3 and 6 μM, respectively. Notably, a mouse model of infection further demonstrated that ligustchuane B could attenuate MRSA virulence in vivo.